1999
DOI: 10.1073/pnas.96.18.10056
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of a higher plant antenna protein provides identification of chromophores bound into multiple sites

Abstract: The chromophore-binding properties of the higher plant light-harvesting protein CP29 have been studied by using site-directed mutagenesis of pigment-binding residues. Overexpression of the apoproteins in bacteria was followed by reconstitution in vitro with purified pigments, thus obtaining a family of mutant CP29 proteins lacking individual chromophorebinding sites. Biochemical characterization allowed identification of the eight porphyrins and two xanthophyll-binding sites. It is shown that the four porphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
327
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(385 citation statements)
references
References 37 publications
57
327
1
Order By: Relevance
“…Considering that the 675-nm band is the only negative contribution observed in the spectra, it can be concluded that the monomers are isoenergetics. Similar values for the absorption of monomeric Chl A5 were found in LHCII and CP29 (21,22), thus supporting the present conclusion. We have to highlight the fact that the bandwidth of the red-most transition is very large, as is expected in the case of a Chl dimer because of strong electronphonon coupling, whereas the absorption at 675 nm has the FWHM typical of a Chl monomer.…”
Section: Is the Presence Of Asn As Ligand For Chl A5 Sufficient To Lesupporting
confidence: 80%
See 3 more Smart Citations
“…Considering that the 675-nm band is the only negative contribution observed in the spectra, it can be concluded that the monomers are isoenergetics. Similar values for the absorption of monomeric Chl A5 were found in LHCII and CP29 (21,22), thus supporting the present conclusion. We have to highlight the fact that the bandwidth of the red-most transition is very large, as is expected in the case of a Chl dimer because of strong electronphonon coupling, whereas the absorption at 675 nm has the FWHM typical of a Chl monomer.…”
Section: Is the Presence Of Asn As Ligand For Chl A5 Sufficient To Lesupporting
confidence: 80%
“…It has to be considered that the His versus Asn substitution appears to be a usual tool for modulation of Chl-Chl interactions in Lhc proteins; Chl A2, when coordinated by Asn in Lhcb1, establishes excitonic interactions with neighbor pigments, namely Chl B2 and Chl A4. This interaction is absent in Lhcb4 (CP29) in which His is the ligand for Chl A2 (21,22) and again present in the Asn-bearing Lhcb5 (CP26), whose overall biochemical and spectral characteristics are very close to those of CP29 (19).…”
Section: Is Asn As Ligand For Chl A5 Necessary To Yield To the Low mentioning
confidence: 96%
See 2 more Smart Citations
“…2A). Reconstitution and mutagenesis experiments on Chl a͞b proteins suggest that at least some of the eight Chl-binding sites common to all Chl a͞b proteins (10, 11) can ligate either Chl a or b (11)(12)(13). One of these proteins can even be reconstituted almost exclusively with Chl b, although with somewhat altered energy transfer characteristics (13).…”
mentioning
confidence: 99%